ANALISIS PENGARUH PROMOSI TERHADAP PENJUALAN TAJUNG PADA CV ILHAM PALEMBANG - Erna AR (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
This study aims to determine the extent of promotions carried out by companies in increasing sales and also to find out whether promotional costs have an influence on sales volume. The analysis technique used Linear Regression results of calculations Y = 904.45 + 1.10 (X) From the calculations above the increase in promotional costs will increase sales volume. Correlation Analysis Results can be r = 0.8772 or close to 1 this means the relationship between promotional costs and the number of sales has a strong and direct relationship or in other words the promotional costs incurred by the company affect the number of sales.